Integrated Approach of Physiotherapy with Ayurveda in Management of Tethered Cord Syndrome: A Case Report - Shreya Mukund Kulkarni; Vijay Kage; Ramesh Killedar; Peeyoosha Gurudut; Aarti Welling (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Tethered Cord Syndrome (TCS) is a rare neurological condition caused by pathological anchoring of the spinal cord, resulting in abnormal stretching and progressive neurological deficits. Although TCS is commonly diagnosed in childhood, adult-onset cases present diagnostic and therapeutic challenges due to delayed recognition and varied clinical manifestations. The present case report describes a 38-year-old male presenting with chronic low back pain, progressive lower limb weakness and bilateral lower limb tremors, leading to impaired functional mobility and reduced quality of life. Magnetic Resonance Imaging (MRI) revealed thickening of the filum terminale, confirming the diagnosis of adult TCS. As the patient preferred conservative care, a 4-week integrated treatment program combining structured physiotherapy and Ayurveda interventions was implemented. Physiotherapy focused on pain relief, muscle strengthening, flexibility and functional rehabilitation, while Ayurveda therapies aimed to enhance neuromuscular balance and provide symptomatic relief. Clinical progress was monitored through periodic neurological and functional assessments. Following the intervention, the patient demonstrated significant improvements in pain intensity, muscle strength, lower limb tremors and overall functional performance, with no adverse effects reported. The present case suggests that integrative, non surgical management may be beneficial in adult TCS patients opting for conservative treatment and highlights the need for further controlled studies.